Central Gαi2 Protein Mediated Neuro-Hormonal Control of Blood Pressure and Salt Sensitivity - Amraei, Razie; Moreira, Jesse D.; Wainford, Richard D. (Frontiers in Endocrinology, 2022)
Hypertension, a major public health issue, is estimated to contribute to 10% of all deaths worldwide. Further, the salt sensitivity of blood pressure is a critical risk factor for the development of hypertension. The hypothalamic paraventricular nucleus (PVN) coordinates neuro-hormonal responses to alterations in plasma sodium and osmolality and multiple G Protein-Coupled Receptors (GPCRs) are involved in fluid and electrolyte homeostasis. In acute animal studies, our laboratory has shown that central Gαi/o subunit protein signal transduction mediates hypotensive and bradycardic responses and that Gz/q, proteins mediate the release of arginine vasopressin (AVP) and subsequent aquaretic responses to acute pharmacological stimuli. Extending these studies, our laboratory has shown that central Gαi2 proteins selectively mediate the hypotensive, sympathoinhibitory and natriuretic responses to acute pharmacological activation of GPCRs and in response to acute physiological challenges to fluid and electrolyte balance. In addition, following chronically elevated dietary sodium intake, salt resistant rats demonstrate site-specific and subunit-specific upregulation of Gαi2 proteins in the PVN, resulting in sympathoinhibition and normotension. In contrast, chronic dietary sodium intake in salt sensitive animals, which fail to upregulate PVN Gαi2 proteins, results in the absence of dietary sodium-evoked sympathoinhibition and salt sensitive hypertension. Using in situ hybridization, we observed that Gαi2 expressing neurons in parvocellular division of the PVN strongly (85%) colocalize with GABAergic neurons. Our data suggest that central Gαi2 protein-dependent responses to an acute isotonic volume expansion (VE) and elevated dietary sodium intake are mediated by the peripheral sensory afferent renal nerves and do not depend on the anteroventral third ventricle (AV3V) sodium sensitive region or the actions of central angiotensin II type 1 receptors. Our translational human genomic studies have identified three G protein subunit alpha I2 (GNAI2) single nucleotide polymorphisms (SNPs) as potential biomarkers in individuals with salt sensitivity and essential hypertension. Collectively, PVN Gαi2 proteins-gated pathways appear to be highly conserved in salt resistance to counter the effects of acute and chronic challenges to fluid and electrolyte homeostasis on blood pressure via a renal sympathetic nerve-dependent mechanism.